Group portrait of participants at the annual Garden City Chevrolet Company picnic - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of the participants of the annual Garden City Chevrolet Company picnic, held in 1948 at an unknown location. A set of participants are holding up a sign that reads "Garden City Chevrolet Co. Annual Picnic 1948."